Investigation of the thermal and microstructural changes of CuAlNiNb quaternary shape memory alloys by different niobium amount - Cirak, Z. Deniz; Kok, Mediha (Springer Heidelberg, 2018)
Among the CuAl-based alloys, the most useful one is the CuAlNi ternary shape memory alloy. There are studies on the development of these alloys. In this study, beta-Nb element was added to the CuAlNi alloy as a fourth element at various rates. The effect of the doped Nb element on the martensitic transformation temperature of the CuAlNi-shape memory alloy was determined by differential scanning calorimetry (DSC). When the value of transformation temperature in quaternary CuAlNi alloys increased, as a result, austenite start and martensite start temperatures are close to each other. Crystalline structure analysis with X-ray diffractometer revealed that beta 1' and gamma 1' phases were found in Cu83.5Ni3.5Al13 alloy, which is the main alloy, while crystal structure of beta-Nb phase was also found with Nb addition. Likewise, the same phases were determined by SEM-EDX analysis. In addition, the result of Vickers hardness measurements indicated that the hardness value of CuAlNi alloys increased by extent of contribution of Nb.
Keywords: Phase-Transformation Characteristics; Mechanical-Properties; Heat-Treatment; Stability; Additions; Behavior; Element; Cobalt